1995
DOI: 10.1099/0022-1317-76-9-2337
|View full text |Cite
|
Sign up to set email alerts
|

Association of hepatitis C virus particles with immunoglobulin: a mechanism for persistent infection

Abstract: The physical properties of hepatitis C virus (HCV) particles were determined by ultracentrifugation on 20-60 % isopycnic sucrose density gradients. We report that (i) two populations of HCV particles were found in the sera of patients with chronic HCV infection [at high density (1.186-1.213 g/ml) and at low density (1.099-1.127 g/ml)], (ii) virus particles with high density values were associated with immunoglobulin, and (iii) virus particles with low density values accumulated base changes within a hypervaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 22 publications
2
48
0
Order By: Relevance
“…Some HCV particles with a high density have been reported to be associated with immunoglobulins (8,15,20,42). To search for immunoglobulins, we subjected the three fractions to SDS-PAGE and Western blotting with anti-immunoglobulin antibodies (Fig.…”
Section: Analysis Of Very-low- Intermediate- and Low-density Plasmamentioning
confidence: 99%
“…Some HCV particles with a high density have been reported to be associated with immunoglobulins (8,15,20,42). To search for immunoglobulins, we subjected the three fractions to SDS-PAGE and Western blotting with anti-immunoglobulin antibodies (Fig.…”
Section: Analysis Of Very-low- Intermediate- and Low-density Plasmamentioning
confidence: 99%
“…Different buoyant densities of HCV derived from patient sera have been reported. HCVimmunoglobulin complexes from the sera of chronically infected patients exhibit an intermediate density ranging between 1.18 and 1.21 g/ml (12). A second population of HCV with a very low density of ϳ1.08 to 1.11 g/ml in sucrose was observed and most likely represents the infectious form of the virus (10,31,52).…”
mentioning
confidence: 99%
“…Furthermore, the virus population in these sera is very heterogeneous, as viral particles associate with immunoglobulins (12,31,68) and ␤-lipoproteins (52,57,67), complicating direct morphological studies. Different buoyant densities of HCV derived from patient sera have been reported.…”
mentioning
confidence: 99%
“…Determination of the buoyant density ofvirus particles showed that the majority of infectivity is found in fractions of 1.03-1.1 g mL-l (Bradley et al, 1991;Carrick et al, 1992;Hijikata et al, 1993a). In addition, particles with lower and higher densities are also detected, corresponding to complexes with cellular lipoproteins and immunoglobulins, respectively (Miyamoto et al, 1992;Hijikata et al, 1993a;Thomssen et al, 1992Thomssen et al, , 1993Choo et al, 1995).…”
Section: Nature Of the Infectious Agentmentioning
confidence: 99%